Poverty during Covid-19 Pandemic in Indonesia: A Case Study in Java-Bali Region - Haning Romdiati; Dwiyanti Kusumaningrum (Universitas Gadjah Mada, 2021)
Indonesia has greatly affected by COVID-19 outbreak. This study shows that health crisis during COVID-19 pandemic has caused the rise of new poor seen from the increase of poverty rates, both at the national, regional, and local levels. The increase in poverty occurred in all provinces which is associated with the magnitude of pandemic. In this study, we highlight poverty in the provinces of Java-Bali region as the most affected areas of the outbreak. Among the 128 regencies/cities, the six top highest increase in poverty are regencies/cities that located in small islands and coastal regions. The highest increase was experienced by Kepulauan Seribu by 2,78% of increase. This follows by increase in Sampang Regency (2,07%), North Jakarta (1,74%), Bangkalan Regency (1,66%), and Indramayu Regency (1,59%) respectively. This study shows that the uncertainty in the time of COVID-19 has made precarity among productive working groups. Migrant workers especially in urban areas are more vulnerable due to ‘lockdown’ policies. In addition, we also found that poverty in small islands and coastal cities are severely affected. Further research needs to be done to elaborate this finding to anticipate poverty in Indonesia in the future when the uncertainty of COVID-19 continues to this day.